Postural stability of young adults during momentary absence of vision - Costa, Regina Maria Carvalho Leme; Goroso, Daniel Gustavo; Lopes, José Augusto Fernandes (Acta Fisiátrica, 2009)
This work aimed at the analysis of the postural stability of young adults in the momentary absence of vision (MAV), in the movement of the trunk towards an upright stance. A system of two force platforms (one for each foot) was utilized, with a sampling frequency of 1000Hz, and an imaging system with a sampling frequency of 200Hz; both systems were synchronized. Ground reaction forces (GRF) in each support foot were obtained and the center of pressure (COP) was calculated. The center of gravity (COG) was also obtained through a tridimensional reconstruction of 8 cameras. The gross kinetic and kinematic signals were filtered, using a Butterworth filter of 6th and 4th order, respectively, with a cutoff frequency of 12Hz. Data was collected from 10 individuals, young adult males, with average age of 25.6 ± 2.3 years, under two visual conditions: (1) Preserved Vision (PV) and (2) Momentary Absence of Vision (MAV), and 5 trials were made for each visual condition. The movement task, referred to as self-perturbation, started from the initial trunk flexion position (90o) towards the upright stance. The amplitude of the vector module // was defined as the study variable in the intervals before the perturbation, perturbation, and post-perturbation, in order to quantify the recovery time of the stability in the post-perturbation interval. The module vector amplitude // was adjusted with an exponential curve. The average values obtained for the stability recovery time were: 779.6ms (±138.6) for the PV condition and 404.8ms (±170.2) for the MAV condition. The Kolmogorov-Smirnov test was applied to verify the normality of the variables: stability recovery time and post-perturbation amplitude (p<0.05). Afterwards, the Student´s t test was applied for the paired data and the bidirectional ANOVA test was applied for the 5 trials of each visual condition. Significant differences (P<0.05) were noted for the variables analyzed in the post-perturbation interval. It was concluded that the MAV individuals, when compared to the PV individuals, utilized rapid neuromuscular adjustment mechanisms to stabilize themselves in the upright stance and not to fall.